To Question оf Using Power Reserve оf Power-and-Heat Supply Turbine Plants - S. A. Kachan; I. N. Baranovski (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers possibilities and limitations of various methods for obtaining power re-serve at power-and-heat supply turbo-generator sets.Approximate values of specific heat rate and quantity of reserve power and rate of its obtaining for various turbine plants are given in the paper.